2008
DOI: 10.3402/ijch.v67i5.18352
|View full text |Cite
|
Sign up to set email alerts
|

Hearing outcomes after mobile ear surgery for chronic otitis media in Greenland

Abstract: Objectives. Chronic otitis media (COM) with hearing loss (HL) occurs frequently in many populations with limited access to specialized treatment. This article reports on the hearing outcomes following mobile ear surgery in Greenland. Study design. The study was longitudinal and prospective with pre-and post-operative followup data compiled at 1-and 2-year intervals. Methods. Selection criterion included individuals with COM with or without suppuration (CSOM) and with associated HL. Hearing tests were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The study showed a long-term ‘take rate’ (i.e. the percentage of total ears with closed perforations) of 76 per cent and a long-term median air conduction PTA hearing gain of 12 dB 9 , 16 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The study showed a long-term ‘take rate’ (i.e. the percentage of total ears with closed perforations) of 76 per cent and a long-term median air conduction PTA hearing gain of 12 dB 9 , 16 …”
Section: Discussionmentioning
confidence: 95%
“…Our group published recently the results of 274 cases of unilateral ear surgery for chronic otitis media and CSOM carried out in a mobile setting in Greenland 9 , 16 . Two or (at most) three patients (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those that do include them report the results in different ways (Table I). [1][2][3][4][5][6][7][8][9][10] Hearing improvement is reported in a variable proportion of patients, but this is partly because of the different ways in which the results are presented. The degree of audiometric hearing improvement correlates with improved quality of life, as measured by the Glasgow Benefit Inventory, and is therefore a useful outcome measure.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been designed to accommodate the specific need for culturally sensitive research in Greenland and across the Arctic, as described in the present research strategy (51). To a lesser degree, health research has included projects on quality, encompassing large, international collaborative projects such as the International Polar Year project on infectious disease surveillance covering the whole Arctic region (52), but also Nordic (53), national (48,54,55) and local (56,57) projects on aspects of quality in care. To improve the health care system, more research is needed on health care management, including topics such as culturally sensitive implementation of health care, evaluation of best practice, cost-benefit analysis of resource allocation, as well as clinical quality and how it can be facilitated.…”
Section: The Future: Improving Data and Securing Qualitymentioning
confidence: 99%